2018
DOI: 10.21608/epsj.2018.17107
|View full text |Cite
|
Sign up to set email alerts
|

Response of Growing Rabbits to Stoking Density and Dietary Supplementation With Ascorbic Acid, and Vitamin E Under Summer Conditions

Abstract: In factorial arrangement of treatments (2×4), an experiment was conducted to evaluate the effects of stocking density and vitamin C, vitamin E and their combination on growth performance of Californian rabbits during summer season (high ambient temperature of 36.4 • C and maximum relative humidity of 97%). Sixty unsexed 7-week-old rabbits were distributed into 8 groups of three replications each. The rabbits were kept in battery cages at two stocking densities; 10 or 15 rabbits/m 2 and were fed on four experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…The current results are defined that T2 rabbits had more (P<0.05) weight of hot carcass than T1 rabbits. The present results are agreement with those reported by Sherif (2018) and Belles et al (2019) who established that the amount of dietary vitamin E has positively correlated with that found in the hot meat carcass. In this context, Dalle Zotte et al (2020) found that greater (P>0.05) weight of slaughter and chilled carcass was 3021 and 1764 g in vitamin E rabbits than 2956 and 1385 g in the control rabbits, respectively.…”
Section: Carcass Characteristicssupporting
confidence: 94%
“…The current results are defined that T2 rabbits had more (P<0.05) weight of hot carcass than T1 rabbits. The present results are agreement with those reported by Sherif (2018) and Belles et al (2019) who established that the amount of dietary vitamin E has positively correlated with that found in the hot meat carcass. In this context, Dalle Zotte et al (2020) found that greater (P>0.05) weight of slaughter and chilled carcass was 3021 and 1764 g in vitamin E rabbits than 2956 and 1385 g in the control rabbits, respectively.…”
Section: Carcass Characteristicssupporting
confidence: 94%
“…The significantly (P<0.05) higher of LDL was observed with G1 rabbits than G2 rabbits. In harmony with the present results of some authors (Sayed-Ahmed et al, 2018, Sherif, 2018, and Al-Kurdy et al, 2021 they asserted that addition of vitamin C to diet could be improved biochemical blood parameters of rabbits. Furthermore, Hassan et al (2021) recoded that using of 1.0 g of vitamin C/kg diet can change rabbits plasma blood concentration included total protein (g/dL), globulin (g/dl), total cholesterol (mg/dL), triglyceride (mg/dL), LDL (mg /dL), total lipids (mg/dL) and ascorbic acid (mg/L) up to 6.…”
Section: Biochemical Parameterssupporting
confidence: 91%
“…Furthermore, Sayed-Ahmed et al (2018) suggested that rabbits during winter had better growing performance included FLBW, DBWG and DFI up to 2167.00, 25.97 and 112.31gm with 0.50 g of vitamin C/kg diet and 2182, 26.44 and 116.34 gm with 1.5g of vitamin C/kg diet than 2019, 23.62, 116.81 gm with control rabbit, respectively. Indeed, Sherif (2018) showed that weekly administration of vitamin C with 200mg/kg diet resulted positively in FLBW, DBWG, DFI and FCR up to 2078.0, 23.9, 90.6 gm and 3.83% compared to 2065, 20.9, 91.2 gm and 4.40% in control rabbits; respectively. Similarly, Hamza (2019) demonstrated that dietary vitamin C supplementation in rabbits at levels of 0.5, 1.0 and 1.5 g/kg diet could be increased final BW, BWG and FCR, while DFI was not changed.…”
Section: Growing Parametersmentioning
confidence: 99%
“…Conversely, Alefzadeh et al [42] found that dietary orange peel powder at 2% reduced weight of most of the carcass parts in broilers. Sherif [43] concluded that AA supplementation at a level of 0.5 g/kg diet was positively affected carcass yield and total edible parts percentages of rabbits. Based on the present results, The use of OPE and TPE supplementations in the rabbit diets had beneficial effects in reducing abdominal, kidneys and back fat in rabbits carcass and that may be due to the that ascorbic acid has an antioxidant feature may prevent lipid peroxidation [44].…”
Section: Discussionmentioning
confidence: 99%
“…Our outcomes regarding blood biochemicals are in harmony with those obtained by Sayed and Abdel-Azeem [53] who showed that serum protein, albumin and globulin of rabbits were not affected by different levels of dried tomato seeds (10-30%). Sherif [43] concluded that rabbits fed diet containing 0.5 g vitamin C had low plasma cholesterol levels. The low levels of plasma cholesterol and LDL-cholesterol in our work may be associated with the antioxidant ability of ascorbic acid which is mainly attributed to its role as a cofactor for the enzyme 7-alpha-hydroxylase, the rate limiting enzyme in the transformation of cholesterol to bile acids [54].…”
Section: Discussionmentioning
confidence: 99%